Удмурты. На земле древних алангасаров - Грязев Георгий Геннадьевич (Удмуртия, 2020)
Экземпляры: ф.10 (20230202) / Инвентарный номер: 63142 / Цена: / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: У 30 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)